2024
DOI: 10.14336/ad.2023.0608
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease Puzzle: Delving into Pathogenesis Hypotheses

Abstract: Alzheimer's disease (AD) is a prevalent neurodegenerative disease characterized by both amnestic and non-amnestic clinical manifestations. It accounts for approximately 60-70% of all dementia cases worldwide. With the increasing number of AD patients, elucidating underlying mechanisms and developing corresponding interventional strategies are necessary. Hypotheses about AD such as amyloid cascade, Tau hyper-phosphorylation, neuroinflammation, oxidative stress, mitochondrial dysfunction, cholinergic, and vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 292 publications
0
8
0
Order By: Relevance
“…While abundant evidence underscores the role of neuroinflammation in the pathogenesis of AD, its position as a cause and consequences remain undetermined [ 48 ]. Besides the early changes of inflammatory proteins, GFAP has also been linked to brain Aβ pathology [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While abundant evidence underscores the role of neuroinflammation in the pathogenesis of AD, its position as a cause and consequences remain undetermined [ 48 ]. Besides the early changes of inflammatory proteins, GFAP has also been linked to brain Aβ pathology [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a large genome-wide association study has also shown a causal relationship between neuroinflammation and ADRD [ 50 ]. However, neuroinflammation can be triggered by the neurodegenerative processes of AD, such as tau dysfunction and Aβ deposition [ 48 , 51 , 52 ], potentially rendering it a non-specific response. In our study with ~ 50,000 participants, we found robust correlations between peripheral GFAP and NfL expression with AD-GRS APOE*E4 alleles, suggesting shared genetic factors driving early neuroinflammation and neurodegenerative changes in dementia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathogenesis of AD is not clear. At present, there are three leading hypotheses, namely the cholinergic, amyloid, and tau hypotheses . As there is no specific drug to treat AD, intervention implemented in the early stage of memory impairments is currently the only therapeutic strategy to alleviate the symptoms and development of AD.…”
Section: Neuroprotective Effects Of Bioactive Peptides In Cns Diseasesmentioning
confidence: 99%
“…At present, there are three leading hypotheses, namely the cholinergic, amyloid, and tau hypotheses. 12 As there is no specific drug to treat AD, intervention implemented in the early stage of memory impairments is currently the only therapeutic strategy to alleviate the symptoms and development of AD. Many peptides of plant 13 and animal 14 origin are known to improve memory impairments against the above hypothesis.…”
Section: Admentioning
confidence: 99%
“…In the central nervous system, it is involved in growth, development, and aging-regulating neural plasticity, differentiation, proliferation, and clearance of aged neurons . It is also involved in a large variety of pathophysiological conditions, such as different myasthenic syndromes, myasthenia gravis, in particular, Alzheimer’s disease (AD), the most prevalent neurodegenerative disorder in the elderly characterized by progressive cognitive decline, Tourette syndrome, and nocturnal frontal lobe epilepsies, among others. Although the occurrence of these different pathophysiological conditions is due to different causes–multifactorial events in some cases–from a therapeutic point of view, they can be classified into two main groups. One group includes the first two above-mentioned pathological conditions, among others, sharing the “cholinergic hypothesis” that is related to a deficit of functional nAChR, and hence nAChR function potentiation is the therapeutic goal (muscle nAChR in the case of myasthenic syndromes and neuronal nAChR for AD, becoming α7 nAChR increasingly more important for AD pathology).…”
Section: Introductionmentioning
confidence: 99%